IMPLEMENTASI IJÄRAH DAN IMBT PADA BANK BRI SYARIAH CABANG YOGYAKARTA - Sartika, Mila; Adinugraha, Hendri Hermawan (Economica: Jurnal Ekonomi Islam, 2016)
The development of Islamic banking is relatively significant modifications to the current demands of product variants resulted in raising funds and financing at Islamic banking. The concept of ijÄrah and ijÄrah muntahiyah bi al-tamlÄ«k (IMBT) both are one example of financial products and services in Islamic banking. By the mindless, this paper aims to describe the concept of ijÄrah and IMBT on Islamic banking and explained at the level of practice and compliance with the law analyze normative (al-Qurâan, Hadith, and the MUI Fatwa/DSN) and positive law (the Compilation of Sharia Economic Law which issued by the Supreme Court). This research uses a field of research that is descriptive analytical study then combined with the library to produce a comprehensive description of the ijÄrah and IMBT. Data analysis techniques starting from the identification of problems, data collection, solve problems which eventually led to the solution in the form of a conclusion. From the findings it can be concluded that the implementation of ijÄrah and IMBT as financing products at Bank BRI Syariah Cabang Yogyakarta is done by the bank to buy what is desired by the customer (such as home and vehicle), then rent it to their bank, at the end of the contract/agreement the bank gives them the option, to have the leased goods bought by way of BRI Sharia (IMBT), or by handing it back to BRI sharia (ijÄrah). In practice, the operational foundation based on the Sharia Board of the National Fatwa No. 09/DSNMUI/IV2003 the Compilation Economics and Shariah Law Chapter XI of ijÄrah and IMBT.